(3GdCOhGQ GdYfUQjI GdeSJNQLI ef GdRHQLOs - (3CMeO Hf GdZRj GdMfajs
(3ChdgG (B:s
(3GdMeO ddg GdhGMO dGef YOO eMShH GdefaQO HYde HhGWf GdYHhQ GdPi Yde ef GdZjH ecfhf s
(3BNQgG (B:s
(3Ke JSJCfa Yedc CjVkG hJbhd C e e hgPG BNQ eG GdaGg QShd GdEdgGe Ydi GdYHO GdeSJgGe hUdi Gddg Ydi SjOfG eMeO SjO GdCfGe hBdg hUMGHJg GdcQGe hSde JSdjekG OGFekG Ydi GdOhGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3ESchQjGd (B(1693/2) s
Keywords: (3GdcjejGA h GdWHjYjGJs